PENERAPAN ETIKA BISNIS SEBAGAI FONDASI KEBERLANJUTAN DAN KEPERCAYAAN DALAM ORGANISASI MASA KINI - Sella Rindiani; Nurlaila Intan Cahyani; Muhammad Ikhsan; Ismi Fauziah (Taksasila Edukasi Insani, 2026)
The application of business ethics has become a fundamental pillar for modern organizations striving to achieve sustainability and strengthen stakeholder trust. The core issue addressed in this study is the growing complexity of the business environment, which requires organizations to uphold integrity, transparency, and social responsibility as part of sustainable business practices. This study aims to examine how ethical principles contribute to organizational stability, enhance corporate reputation, and support long-term relationships with employees, customers, and strategic partners. This research employs a literature-based approach by reviewing scientific journals, academic books, and relevant documents discussing business ethics and organizational sustainability. The findings reveal that consistent implementation of ethical practices reinforces governance structures, minimizes potential violations, and increases public trust in the organization. Additionally, the integration of ethical values into decision-making processes promotes adaptive and responsible organizational performance. Therefore, business ethics function not only as moral guidelines but also as a strategic foundation for fostering long-term sustainability in contemporary organizations. Keywords : business ethics, sustainability, trust, governance, organization.